Development of Rechargeable Lawn Mower - Hanafi, Dirman; Afrianto, Muhamad Wendi; Kwad, Ayad Mahmood; Wahid, Herman; Ghazali, Rozaimi; Gunardi, Yudhi (International Journal of Electrical, Energy and Power System Engineering, 2023)
Lawn mower is device to mow grass. The lawn mower will be having a problem such as the lawn mower widely used around by handle manually with hand. Next, the power source for lawn mowers is from petrol energy. That energy is nonrenewable energy and has bad impacts on the environment and people. In this paper, a prototype of lawn mower is designed and fabricated with its operation movement system through the Smartphone via Wi-Fi connection. The lawn mower is powered using the sealed acid battery that it can charging by using the photovoltaic cell or AC voltage source. The development of rechargeable lawn mower using ESP32 to keep and process data before sending to the webpage IP Address 192.168.4.1 to show the control movement of lawn mower via Smartphone. Based on experimental test results, the lawn mower was able to control its movement via a smartphone through a Wi-Fi connection. Next, the results were revealing the ability of solar panels for 2 hours and AC voltage for 1 hour to fully charged the sealed lead-acid batteries. Finally, a grass trim performance test was carried out on a lawn mower in the yard of the house and the result was that the grass could be cut. After that, the battery consumption of lawn mower operation for 1 hour was obtained the result around 50% of the capacity which is fully discharge because occurs the maximum depth of discharge of sealed lead acid batteries.